Facial expression coding in children and adolescents with autism: Reduced adaptability but intact norm‐based coding. (19th July 2017) - Rhodes, Gillian; Burton, Nichola; Jeffery, Linda; Read, Ainsley; Taylor, Libby; Ewing, Louise
Abstract : Individuals with autism spectrum disorder (ASD) can have difficulty recognizing emotional expressions. Here, we asked whether the underlying perceptual coding of expression is disrupted. Typical individuals code expression relative to a perceptual (average) norm that is continuously updated by experience. This adaptability of face‐coding mechanisms has been linked to performance on various face tasks. We used an adaptation aftereffect paradigm to characterize expression coding in children and adolescents with autism. We asked whether face expression coding is less adaptable in autism and whether there is any fundamental disruption of norm‐based coding. If expression coding is norm‐based, then the face aftereffects should increase with adaptor expression strength (distance from the average expression). We observed this pattern in both autistic and typically developing participants, suggesting that norm‐based coding is fundamentally intact in autism. Critically, however, expression aftereffects were reduced in the autism group, indicating that expression‐coding mechanisms are less readily tuned by experience. Reduced adaptability has also been reported for coding of face identity and gaze direction. Thus, there appears to be a pervasive lack of adaptability in face‐coding mechanisms in autism, which could contribute to face processing and broader social difficulties in the disorder.